Od świata życia do świata wiedzy. Na podstawie koncepcji Edmunda Husserla - Ryk, Andrzej (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The phenomenology of Edmund Husserl proposes a new way of understanding the basics of research methodology. It analyzes the world of everyday experience and survive thanks to reveal permanent and unchanging structure of reality. The design of such research includes the fact that so far it was often denied, rejected as unscientific and without scientific basis. Meanwhile, Husserl indicates that a positivist thought of abandoning the world of everyday experience and the experience made a fundamental error. There is no knowledge of the world without the world - the surrounding world and directly experienced by the knowing subject. The world is not a world of disorder and chaos. Therefore, the purpose of phenomenological research is unveiling its permanent structure.
Keywords: methodology; phenomenology; the world of everyday life